PID and Predictive Control of Electrical Drives and Power Converters using MATLAB / Simulink - Wang, Liuping; Chai, Shan; Yoo, Dae; Gan, Lu; Ng, Ki (IEEE Press Series on Power Engineering, 2015)
Electrical drives play a critical role in electromechanical energy conversions. They are the fundamental building blocks in manufacturing, transportation, mineral processing, wind energy and many other industries. This book presents methods for design and implementation of PID and predictive control of electrical drives and grid connected three phase power converters with emphasis on meeting operational constraints while optimizing performance. The authors share their experiences in actual design and implementation of the control systems on laboratory test-beds, taking readers from the fundamentals through to the sophisticated design and analysis. Brings together both classical control systems and predictive control systems in a logical style from introductory through to advanced levels Demonstrates how simulation and experimental results are used to support theoretical analysis and the proposed design algorithms Gives MATLAB and Simulink tutorials to show the readers how to apply theoretical concepts Includes MATLAB and Simulink software for teaching purposes A companion website with Simulink/MATLAB and xPC Target Programs is available PID and Predictive Control of Electrical Drives and Power Converters using MATLAB/Simulink is an excellent resource for researchers and industrial engineers, as well as graduate students and senior undergraduates on electrical engineering courses.